PEMANFAATAN Trichoderma sp DAN DREGS UNTUK PERTUMBUHAN DAN SERANGANPENYAKTrFISIOLOGISBIBITKELAPASAWIT PADAMEDIUMGAMBUTDIPEMBIBITANAWAL - Vetti Elfina; Wardati ' (Jurnal Sagu, 2010)
Oil palm {Elaeis guineentis Jacq) represents file most im|iorfant commodity in plantation sector.The problems often faced in oil palm agriculture effort is the availability of quality seed and avaOability ofpotential and fertile soil. Peat soil has some weaknesses such as its acidity (pH) and slow decompositionprocess. One method to overcome the acidity of peat soil is by using dregs and decomposition process can beimproved by applying Trichoderma sp. The objective of this research was to know the influence of interactionand primary factor of Trichoderma sp and dregs application for oil palm seed growth and physiologicalcondition at peat medium In pre nursery. It was conducted from September 2006 to Febrvari 2007. Theparameters of this research were the height of seed, leaf amount, shoot dry weight, root dry weight, and shoot-root ratio. The treatment of Trichoderma sp of 25 g/ kg of peat with dregs of 30 g/kg of peat had significanteRect to height of seed, and shoot wet weight. The primary factor tttdregs had significant effect to height ofseed and at dregs dose of 20 g/kg of peat, white leaf amount and shoot-root ratio at dregs dose of 30 g/kg of pea t.The primary factor of Trichoderma sp did not have any significant effect for all parameters.